Screening tests for antibodies to cytomegalovirus: an evaluation of five commercial products. Issue 9 (September 1985) - Grint, P C; Ronalds, C J; Kangro, H O; Campbell-Benzie, A; Ward, F; Hardiman, A E; Heath, R B
Abstract : Four hundred and ninety two samples of serum from blood donors were screened for the presence of antibodies specific to cytomegalovirus using radioimmunoassay, a modified complement fixation test, and five commercially available tests: the Cetus CMV IHA, Abbott CMV total AB EIA, Cytomegalisa Stat EIA, Enzygnost EIA, and Virenz G-CMV EIA. A wide variation in results was found, with only 53.5% of the sera giving total concordance by all methods. Rates of seropositivity in the different tests ranged from 34.9% to 59.3%, with sensitivities ranging from 75.2% to 99.1% compared with the radioimmunoassay. Of 211 sera which gave positive results with four or more of the tests, none was negative by the radioimmunoassay and Abbott EIA, three were negative in Cetus IHA and Enzygnost EIA, and 11 were negative in the modified complement fixation test. Virenz G and Cytomegalisa Stat EIAs, however, gave 40 (19%) and 49 (23.2%), respectively, as negative. The results confirmed the reliability of the radioimmunoassay for the detection of the antibody status to CMV, but this test is too elaborate for a screening procedure. The Abbott EIA and Cetus IHA were found to be the most suitable for this purpose in spite of high false positive rates.